Cd doped Ba (NO3)2 nanoparticle as broadband solar absorber in thin film organic solar cell. Issue 4 (5th December 2019) - Kesinro, Olasunkanmi R.; Boyo, Adenike O.; Hamed, Mohammed S. G.; Akinyemi, Marvel L.; Maaza, Malik; Kasinathan, Kaviyarasu; Mola, Genene Tessema
Abstract: Enhanced photocurrent was observed by embedding Cd doped Ba (NO3 )2 nanoparticle composite in the photoactive layer of bulk heterojunction organic solar cell. The research was conducted based on P3HT: PCBM blend active layer containing Cd doped Ba (NO3 )2 at various concentrations. The best performance of the fabricated devices was found to be dependent on the concentration of the composite nanoparticle. A substantial improvement in PCE of 5.01% compared to 3.25% of the pristine device was obtained. The optical and electrical properties of the fabricated devices were carried out. Also, the structural properties of the nanoparticle composite were established.